Uncovering the Potential of Blockchain Technology in the Accounting Domain: A Bibliometric Analysis and Recent Research Trends - Sri Hardini, Evy Nurhayati; Sibarani, Blasius Erik (Jurnal Akuntansi dan Bisnis, 2025)
Introduction/Main Objectives: Blockchain has earned significant recognition for its capacity to drive transformation and innovation in existing business models and frameworks, including those within the accounting field. This potential has attracted the interest of both academics and practitioners. Background Problems: While research addressing the use of blockchain in accounting has gained momentum, the field presents a disconnected overview of the scope and limits of current knowledge. Novelty: There is a lack of literature reviews that address blockchain technology in the accounting domain. This is important because blockchain technology facilitates record-keeping, increases organizational transparency, streamlines hierarchical structures, aids market disintermediation and source tracking, builds corporate trust, encourages rapid internationalization, and improves accounting functions. Research Methods: This research addresses the gap using bibliometric analysis to synthesize previous literature and 229 scholarly articles based on the Scopus database. Finding/Results: The findings show a well-developed research focus on blockchain technology in specific managerial areas, like finance and supply chain management. However, the conceptual development of the field is still in its early stages. Additionally, a thematic analysis of the existing literature reveals four key research themes: strategy and regulation, enablement and implications, multi-domain deployment, and Bitcoin inefficiency. These themes are crucial as they highlight the main areas of focus within the field of blockchain technology in accounting. Conclusion: The study's findings highlight an urgent need for additional research in these areas of accounting, as current knowledge does not address issues like awareness and consensus on blockchain technology, nor the roles of regulators, auditors, and public administrators in its development and use. This call for further research is crucial and prompts the academic and professional community to take action.